A formal approach to discrete systems theory - Gregor, Jiři (Zielona Góra: Uniwersytet Zielonogórski)
Based on earlier results, an abstract multi-dimensional discrete systems theory is formulated here for further discussion. We believe that a more general framework including variable-parameter systems and nonlinear systems together with some discrete systems which cannot be treated on a common rectangular grid, may widen the scope of possible applications of n-D discrete systems theory. Some general results are summarized and examples are given.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka